Metal-organic framework, organic-inorganic hybrid film, and method for manufacturing a metal-organic framework
Patent Information
- Application Number
- JP2025142662
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-31
- Filing Date
- 2025-08-28
- Publication Date
- 2026-10-14
AI Technical Summary
【0018】 本開示の一態様によれば、プレート状の粒子形状を有し、結晶構造に2種類以上の配位子を有する新規な金属有機フレームワーク、及びその関連技術を提供することにある。
Smart Images

Figure 2026167380000001_ABST
Abstract
Description
[Technical Field]
[0001] This disclosure relates to metal-organic frameworks, organic-inorganic hybrid films, and methods for manufacturing metal-organic frameworks. [Background technology]
[0002] For example, Patent Document 1 describes a material comprising at least one metal-organic framework (MOF), wherein the MOF has pores and comprises zinc ions, an oxalate, and a cycloazocarbil compound other than 3-amino-1,2,4-triazolate.
[0003] Furthermore, Patent Document 2 describes a method for producing a Zn-MOF, comprising the steps of (1) reacting the aforementioned combination of 2 molar equivalents of 1,2,4-triazole or 1,2,4-triazolate and one or more other cycloazocarbil compounds with 1 molar equivalent of oxalate or a combination of oxalate and one or more chelate ligands other than oxalate to form a cycloazocarbil chelate ligand compound as a suspension in a solvent, and (2) 2 molar equivalents of Zn 2+ A method is described which includes the step of adding to the suspension to form the ZnMOF. [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Special Publication No. 2016-516677 [Patent Document 2] Special Publication No. 2021-522226 [Overview of the project] [Problems that the invention aims to solve]
[0005] The inventors of the present disclosure have found that a novel metal-organic framework having a plate-like particle shape and two or more types of ligands in its crystal structure can be produced by a new production method different from the production methods for metal-organic frameworks described in Patent Documents 1 and 2, and have completed the present invention.
[0006] That is, the present disclosure aims to provide a novel metal-organic framework having a plate-like particle shape and two or more types of ligands in its crystal structure, and related technologies thereof. [Means for Solving the Problems]
[0007] To solve the above problems, a metal-organic framework according to one aspect of the present disclosure has the following configuration.
[0008] [1] A metal-organic framework comprising a metal coordinated by two or more types of ligands, A metal-organic framework, wherein the ratio of the major axis to the minor axis in the particle cross-section of the metal-organic framework is 1.7 or more.
[0009] [2] The metal-organic framework according to [1], wherein the metal is zinc.
[0010] [3] The metal-organic framework according to [1] or [2], wherein the metal coordinated by the ligands comprises triazolate and oxalate.
[0011] [4] An organic-inorganic hybrid membrane comprising a metal-organic framework coordinated by two or more types of ligands and a resin, The organic-inorganic hybrid membrane, wherein the ratio of the major axis to the minor axis in the particle cross-section of the metal-organic framework is 1.7 or more, and the content of the metal-organic framework is 30 mass% or more.
[0012] [5] The organic-inorganic hybrid membrane according to [4], wherein the glass transition temperature of the resin is 15°C or lower.
[0013] [6] A composition for forming an organic-inorganic hybrid film, comprising a metal organic framework containing a metal coordinated by two or more types of ligands, and a resin, wherein the ratio of the major axis to the minor axis in the particle cross-section of the metal organic framework is 1.7 or more, and the content of the metal organic framework is 30 mass% or more.
[0014] [7] A method for producing a metal organic framework, wherein a reaction solution before the reaction for the metal organic framework contains a coordination compound and a carboxylic acid compound, and the carboxylic acid compound is a formic acid compound, or contains at least two types of carboxylic acid compounds.
[0015] [8] The method for producing a metal organic framework according to [7], wherein the reaction solution contains a metal compound, the carboxylic acid compound is selected from formic acid and formate, and the formate is sodium formate.
[0016] [9] The method for producing a metal organic framework according to [7], wherein the carboxylic acid compound is zinc formate.
[0017]
[10] The metal compound has a solubility in 100 cm of water at 25°C 3 of 0.05 g or more, and is a zinc compound, according to the method for producing a metal organic framework described in [8]. Effects of the Invention
[0018] According to one aspect of the present disclosure, it is intended to provide a novel metal organic framework having a plate-like particle shape and two or more types of ligands in its crystal structure, and related technologies thereof. Brief Description of the Drawings
[0019] [Figure 1] It is a schematic diagram showing an apparatus for performing a single component gas permeation test. [Figure 2] This is an XRD chart of Zn-MOF produced in Example 1. [Figure 3]Figure 3 shows SEM images of the Zn-MOF produced in Example 2. The right side of Figure 3 shows the side view of the Zn-MOF particles, and the left side shows the top view of the Zn-MOF. [Figure 4] This is the XRD chart of the Zn-MOF produced in Comparative Example 1. [Modes for carrying out the invention]
[0020] <Metal-Organic Framework (MOF)> Metal-organic frameworks (MOFs) are crystalline porous compounds having a regular pore structure formed by a metal and an organic ligand. In this disclosure, the metal ion is a zinc ion, and one embodiment of a metal-organic framework (MOF) includes a zinc ion coordinated to a triazolate and an oxalate, which may have substituents. In the following, metal-organic frameworks containing zinc ions may be referred to as Zn-MOF.
[0021] A metal-organic framework according to one embodiment comprises a metal ion coordinated with two or more ligands, and is typically a metal-organic framework in which a triazole compound, which may have substituents as coordination compounds, and an oxazole compound are coordinated to a zinc ion. Examples of triazolates included in the metal-organic framework according to one embodiment include 1,2,3-triazolate represented by formula (1) and 1,2,4-triazolate represented by formula (2) when coordinated to a zinc ion, with 1,2,4-triazolate being preferred.
[0022] [ka]
[0023] In the formula, R 1 and R 2 These are, independently, an amino group, a nitro group, a methyl group, a mercapto group, and a hydrogen atom. 1and R 2 Preferably, at least one of them is a hydrogen atom, for example, R 1 and R 2 It may also be a hydrogen atom.
[0024] The oxalates contained in the metal-organic framework according to one embodiment refer to oxalate compounds, oxalic acid, and dianions or monoanions of oxalic acid, which is a diacid.
[0025] In one embodiment of the metal-organic framework, the ratio of triazolate to oxalate (triazolate:oxalate (molar ratio)) is preferably 2:1. When the ratio of triazolate to oxalate is as described above, a regular porous structure can be formed, and a metal-organic framework can be formed.
[0026] In one embodiment, the metal-organic framework has a ratio (also called aspect ratio) of the major axis to the minor axis in the particle cross-section of the metal-organic framework of 1.7 or more, preferably 1.8 or more, more preferably 1.9 or more, even more preferably 2.0 or more, and particularly preferably 2.1 or more. The particle cross-section referred to here means the ratio of the thickness direction to the length direction of a plate-shaped particle, and not the aspect ratio of the plane of the plate. The term cross-section is used to explain this. In one embodiment, when the ratio of the major axis to the minor axis in the particle cross-section of the metal-organic framework of 1.7 or more, the metal-organic framework can take the form of a flat plate, and while the film thickness of the organic-inorganic hybrid film described later can be made thin, the organic-inorganic hybrid film can be given high gas separation ability. Furthermore, in one embodiment, the ratio of the major axis to the minor axis in the particle cross-section of the metal-organic framework of 1.7 or more should not be limited, but may be 50 or less.
[0027] The aspect ratio of the metal-organic framework is calculated from the particle cross-section of the metal-organic framework captured in the scanning electron microscope image obtained by photographing a cross-section of an organic-inorganic hybrid film fabricated according to predetermined composition and deposition conditions. For details on the evaluation method of the aspect ratio of the metal-organic framework, please refer to the description in the examples. Although multiple cross-sections exist in the particle cross-section, when the aspect ratio of the particle cross-section obtained according to the method described in the examples is 1.7 or higher, it can be confirmed that the metal-organic framework has a plate-like particle shape, and high gas separation ability can be imparted to the organic-inorganic hybrid film while keeping the film thickness of the organic-inorganic hybrid film thin.
[0028] A metal-organic framework according to one embodiment typically has pores. While the size of the pores in the metal-organic framework according to one embodiment is not particularly limited, it is typically in the range of 0.3 to 2 nm. When the pore size is within this range, excellent carbon dioxide adsorption capacity can be achieved. The pore size of the metal-organic framework according to one embodiment is preferably 0.4 nm to 1.9 nm, more preferably 0.5 nm to 1.8 nm, even more preferably 0.6 nm to 1.7 nm, and particularly preferably 0.7 nm to 1 nm.
[0029] The primary particle size of the metal-organic framework according to one embodiment is typically 100 nm or more, preferably 200 nm or more, and more preferably 500 nm or more, while on the other hand, it is typically 10 μm or less, preferably 5 μm or less, and more preferably 2.5 μm or less. When the primary particle size is within the above range, the surface area of the MOF is appropriate, so access from the MOF surface to the internal pores, which are the main adsorption sites, is good, resulting in a faster adsorption rate and an increase in the amount of adsorption. Here, "primary particle size" is calculated from the particle cross-section of the metal-organic framework captured in a scanning electron microscope image obtained by photographing the cross-section of an organic-inorganic hybrid film fabricated using the synthesized MOF according to predetermined composition and deposition conditions. The particle size is defined as the diameter of a circle (equivalent circle diameter) with an area equal to the projected area of the particle. For details on the evaluation method of the primary particle size of the metal-organic framework, please refer to the description in the examples.
[0030] As described above, the metal-organic framework according to one embodiment has high carbon dioxide adsorption capacity. Specifically, the amount of carbon dioxide adsorbed by a metal-organic framework according to one embodiment is the value of the amount of carbon dioxide adsorbed at an absolute pressure P = 102 kPa, measured by measuring the adsorption isotherm at a temperature of 298 K using a constant volume gas adsorption method with carbon dioxide, after pretreatment by heating at 200°C for 4 hours or more under vacuum conditions. At an absolute pressure of 102 kPa, the carbon dioxide adsorption capacity of the metal-organic framework of this disclosure is typically 1.0 mmol / g or more, preferably 2.0 mmol / g or more, and more preferably 3.0 mmol / g or more, while on the other hand, it is typically 100 mmol / g or less, preferably 50 mmol / g or less, and more preferably 10 mmol / g or less. When the carbon dioxide adsorption capacity is within the above range, a large amount of carbon dioxide can be efficiently adsorbed and desorbed.
[0031] A metal-organic framework according to one embodiment exhibits excellent water resistance. The water resistance of a metal-organic framework can be determined by (i) exposing it to water vapor, (ii) immersing it in water, (iii) immersing it in hot water, or (iv) heating it while immersed in water, and observing the changes in its crystallinity and nitrogen adsorption before and after these processes. Here, the amount of nitrogen adsorbed by the metal-organic framework originates from the pore structure of the metal-organic framework, and the higher the percentage of pores that are maintained, the more nitrogen adsorbed will be maintained even after these treatments.
[0032] (iv) The ratio of nitrogen adsorption amount of the metal-organic framework of this disclosure before and after treatment (after treatment / before treatment) at a relative pressure P / P0 = 0.1, obtained by measuring the nitrogen adsorption isotherm at 77K before and after hydrothermal treatment, is usually 60% or more, preferably 70% or more, more preferably 80% or more, even more preferably 85% or more, and usually 100% or less. When the ratio of nitrogen adsorption amount before and after treatment is within the above range, the adsorbent and the composition containing the adsorbent tend to maintain practical performance over a long period of time.
[0033] [Method for manufacturing metal-organic frameworks] A method for producing a metal-organic framework according to one aspect of this disclosure (hereinafter sometimes referred to as "the production method") includes a coordination compound and a carboxylic acid compound in the reaction solution before the reaction of the metal-organic framework. In the production method according to one aspect, the reaction solution before the reaction is a solution in which at least a portion of the metal compound is dissolved in a solvent, and the coordination compound and the carboxylic acid compound may be added to the solution. Alternatively, in the production method according to one aspect, the reaction solution before the reaction may be a carboxylic acid compound in which the metal compound is a carboxylic acid compound, and the coordination compound may be added to the reaction solution before the reaction.
[0034] A manufacturing method according to one aspect of this disclosure is a novel manufacturing method that can produce a metal-organic framework having a plate-like particle shape by including a formic acid compound or at least two types of carboxylic acid compounds in the reaction solution before the reaction. In the manufacturing method according to one aspect, for example, by including one or more types of coordination compounds in the reaction solution before the reaction, a metal-organic framework in which one or more ligands coordinate to a metal can be produced. That is, by including two or more types of coordination compounds in the reaction solution before the reaction, a metal-organic framework in which two or more ligands coordinate to a metal according to one aspect of this disclosure can be produced.
[0035] <Carboxylic acid compounds> In the production method according to one aspect, a carboxylic acid compound is added to the reaction solution before the reaction. Thereby, the coordination of oxalate to zinc ions during the production of the metal-organic framework is inhibited by the carboxylate derived from the carboxylic acid compound, whereby the coordination of triazolate to zinc ions proceeds preferentially over the coordination of oxalate, and as a result, the metal-organic framework grows with anisotropy, making it possible to obtain a metal-organic framework having a plate-like particle shape. The carboxylic acid compound added to the reaction solution is a carboxylic acid compound other than oxalate. The carboxylic acid compound is preferably a monocarboxylic acid compound. The monocarboxylic acid compound is selected from carboxylic acids and carboxylates, and since a carboxylate does not make the liquid properties acidic, its influence on the formation of the metal-organic framework is limited, it only affects the shape, and a high-purity metal-organic framework can be obtained, which is preferable. As the carboxylate, propionate, acetate, and formate are preferred, acetate and formate are more preferred, and formate is even more preferred. When these carboxylates are used, the size of the carboxylate is small, so the carboxylate easily coordinates temporarily to zinc during synthesis, and anisotropic crystal growth can be effectively promoted. Examples of the counter cation of the carboxylate include alkali metal cations, alkaline earth metal cations, and transition metal ions, and Na + , Zn + , K + , Li + , Mg + are preferred, and Na + , Zn + are particularly preferred. When the counter cations are these, at least a part of the carboxylate easily dissolves in the solvent, and washing after synthesis is also easy, so that a metal-organic framework with a controlled shape can be obtained with high purity. Examples of carboxylic acids include propionic acid, acetic acid, and formic acid, with acetic acid and formic acid being preferred, and formic acid being particularly preferred. When these carboxylic acids are used, the size of the carboxylate derived from the carboxylic acid is small, so the carboxylate can temporarily coordinate with zinc or sodium during synthesis, effectively promoting anisotropic crystal growth. Therefore, zinc formate and sodium formate are particularly preferred, and sodium formate is most preferred. When at least two carboxylic acid compounds are added to the reaction solution, it is preferable that one of the at least two carboxylic acid compounds be a metal compound that serves as a metal source in the metal-organic framework. When a carboxylic acid compound is a metal source in the metal-organic framework, it is also a metal compound. A carboxylic acid compound that serves as a metal source in the metal-organic framework, for example, a zinc source, may also be one embodiment of the metal compound described later.
[0036] <Metal compounds> The metal compound is typically a zinc compound, and as a zinc compound, 100 cm³ of water at 25°C 3 It is preferable to use a zinc compound (hereinafter sometimes referred to as "water-soluble zinc compound") that has a solubility of 0.05 g or more in [the specified solution]. As for zinc compounds, 100 cm³ of water at 25°C 3 The solubility of the zinc compound should be 0.05 g or more. Examples of compounds that satisfy this solubility include zinc formate, zinc acetate, zinc propionate, zinc acetylacetonate, zinc sulfate, zinc chloride, zinc bromide, zinc iodide, zinc nitrate, zinc gluconate, zinc salicylate, and their hydrates. From the viewpoint that the zinc counteranion promotes the deprotonation of triazole in the manufacturing process of the metal-organic framework, zinc acetate, zinc acetylacetonate, zinc sulfate, zinc chloride, zinc nitrate, zinc gluconate, and zinc salicylate are preferred, zinc acetate and zinc acetylacetonate are more preferred, and zinc acetate is particularly preferred. Of these, zinc formate is particularly preferred from the viewpoint of obtaining a plate-shaped metal-organic framework. Two or more of these zinc compounds may be used in combination.
[0037] In one embodiment of the manufacturing method, a zinc compound, a triazole compound which may have substituents, and an oxalate compound are added to a water-containing solvent, and the mixture is stirred and reacted. The zinc compound is 100 cm³ of water at 25°C. 3 It is desirable to use a zinc compound (hereinafter sometimes referred to as a "water-soluble zinc compound") that has a solubility of 0.05 g or more in [the specified solution]. By using such water-soluble zinc compounds, plate-shaped metal-organic frameworks can be easily manufactured. Furthermore, by using zinc compounds with a certain level of solubility in water, the distribution of zinc in the metal-organic framework becomes uniform, resulting in a metal-organic framework with fewer structural defects and a higher proportion of effective pores. Using a metal-organic framework with a uniform zinc distribution has effects such as improving the gas permeability properties of compositions containing the metal-organic framework. Zinc compound in 100 cm³ of water at 25°C 3 Regarding solubility, it is generally preferred to be 0.05 g or more, more preferably 0.1 g or more, even more preferably 1 g or more, and particularly preferably 5 g or more, from the perspective that the distribution of zinc in the metal-organic framework will be uniform. There is no particular upper limit, but it is generally 500 g or less.
[0038] <Triazole compounds> The triazole compounds used in the manufacturing method according to one embodiment include 1,2,3-triazole, 1,2,4-triazole, and their ions, triazolates, which may have substituents. The position of the substituent is not particularly limited, and for example, it may be a compound in which a hydrogen atom bonded to carbon is substituted. Examples of substituents include amino groups, nitro groups, methyl groups, and mercapto groups, and there may be one or two substituents. Among the triazole compounds, 1,2,3-triazole and 1,2,4-triazole are more preferred, and 1,2,4-triazole or their ions are particularly preferred in that they have less steric hindrance with adjacent ligands when forming a metal-organic framework. Furthermore, the form of the triazole compound, which may have substituents, is not limited in this manufacturing method and may be liquid or solid at room temperature. In addition, a solid triazole compound, which may have substituents, can be used after being dissolved or dispersed in a solvent.
[0039] <Oxalate compounds> Oxalate compounds refer to oxalic acid and the dianions or monoanions of oxalic acid, which is a diacid. Examples of oxalate compounds include oxalic acid, lithium oxalate, sodium oxalate, potassium oxalate, potassium hydrogen oxalate, ammonium oxalate, and their hydrates. From the viewpoint of low cost, lithium oxalate, sodium oxalate, potassium oxalate, and their hydrates are preferred, with sodium oxalate and its hydrate being particularly preferred. In this manufacturing method, the form of the oxalate compound is not limited and may be liquid or solid at room temperature. Furthermore, the oxalate compound can be used after being dissolved or dispersed in a solvent.
[0040] <Solvent> In one embodiment of the manufacturing method, a reaction solution is prepared by adding a water-soluble zinc compound, a triazole compound which may have substituents, an oxalate compound, and a formic acid compound to a solvent, and the reaction solution is carried out by stirring and mixing to produce a metal-organic framework. The solvent may contain water, preferably an alcohol, and more preferably an organic solvent such as a lower alcohol having about 1 to 6 carbon atoms that is highly compatible with water. The lower alcohol should be one that is highly compatible with water, for example methanol, ethanol, and isopropanol. Among these, methanol and ethanol are particularly preferred because they have a small number of carbon atoms and are highly polar. Note that one lower alcohol may be used, or two or more may be used in combination; for example, methanol and ethanol may be mixed and used. The mixing ratio of alcohol to water in the mixed solvent is not particularly limited as long as they are miscible. For example, the volume ratio of alcohol to water is preferably in the range of 0.3 to 20 parts alcohol to 1 part water, more preferably in the range of 0.4 to 19 parts alcohol to 1 part water, and even more preferably in the range of 0.6 to 4 parts alcohol to 1 part water. When the mixing ratio of alcohol to water is within this range, the polarity of the solvent is suitable for the formation of the desired metal-organic framework, and it is believed that a metal-organic framework with few impurities and high CO2 adsorption capacity can be obtained.
[0041] <Molar ratio of raw materials> In one embodiment of the manufacturing method, it is preferable to add 0.1 moles to 10 moles, preferably 0.5 moles to 5 moles, and more preferably 0.8 moles to 2.5 moles, of a carboxylic acid compound to 1 mole of zinc compound, and the concentration of the carboxylic acid compound is 0.05 mol / L or higher, preferably 0.1 mol / L or higher, and more preferably 0.2 mol / L or higher, and usually within the range of 5 mol / L or less, preferably 3 mol / L or less, and more preferably 2 mol / L or less, to the reaction solution before the reaction, thereby obtaining a plate-shaped metal-organic framework according to one embodiment.
[0042] In one embodiment of the manufacturing method, it is preferable to add 0.8 moles to 3 moles of optionally substituted triazole compound and 0.4 moles to 0.6 moles of oxalate compound per mole of zinc compound; more preferably 1.5 moles to 2.5 moles of optionally substituted triazole compound and 0.45 moles to 0.55 moles of oxalate compound per mole of zinc compound; and even more preferably 1.8 moles to 2.2 moles of optionally substituted triazole compound and 0.48 moles to 0.52 moles of oxalate compound per mole of zinc compound. Within this range, Zn-MOF can be synthesized efficiently, the yield of Zn-MOF can be improved, the amount of CO2 adsorbed by the obtained metal-organic framework can be increased, and the organic-inorganic hybrid membrane using the obtained metal-organic framework exhibits high gas separation performance due to the low amount of impurities.
[0043] Stoichiometrically, this would involve mixing 1 mole of triazole compound and 0.5 moles of oxalate compound for every mole of zinc compound. However, from the viewpoint of further improving yield, it is more preferable to add 1.5 moles to 2.5 moles of triazole compound and 0.45 moles to 0.55 moles of oxalate compound for every mole of zinc compound.
[0044] <Reaction conditions> The reaction pressure in this manufacturing method is typically atmospheric pressure to self-pressurized pressure. While self-pressurized pressure is used in the case of an autoclave, atmospheric pressure is preferable for simplicity. The reaction temperature in this manufacturing method is acceptable as long as the liquid is in solution at the reaction pressure. The conditions under which the solvent is liquid at atmospheric pressure are typically 0°C to 100°C, preferably 5°C to 80°C, more preferably 10°C to 50°C, and even more preferably 10°C to 35°C. Under these conditions, the product can be manufactured inexpensively and a high yield can be obtained. Since the reaction proceeds even at room temperature (e.g., 25°C), it is particularly preferable to carry out the reaction at room temperature for energy efficiency. Furthermore, while Zn-MOF can be synthesized with a stirring time (reaction time) of 12 hours or more, to further increase the yield and obtain sufficient performance for the manufactured Zn-MOF, a reaction time of 20 hours or more is more preferable, 30 hours or more is even more preferable, and 50 hours or more is also possible. Note that the stirring time refers to the time from immediately after all the raw materials have been added. There are no particular restrictions on the stirring speed; it should be adjusted as appropriate according to the viscosity.
[0045] There are no particular restrictions on the order in which the raw materials are added. The zinc compound, triazole compound, oxalate compound, and carboxylic acid compound may be added to the solvent simultaneously or sequentially. When added sequentially, there are no particular restrictions on the order. For example, the order may be zinc compound, optionally substituted triazole compound, oxalate compound, and carboxylic acid compound. However, adding the zinc compound first is considered preferable because it results in a more uniform distribution of zinc, which can improve the gas permeability of the composition containing the metal-organic framework, for example. Here, the zinc compound is preferably zinc acetate and / or zinc formate. Furthermore, the second and subsequent substances added to the solvent may be added directly, or they may be dissolved or dispersed in another solvent before being added. The type of solvent used in this case is the same as that used above. The same applies to the mixing ratio of the solvents. Here, the mixing ratio of the solvents refers to the ratio of each compound to the total amount of solvent at the time all compounds have been added. When adding compounds sequentially, there are no particular restrictions on the interval between additions, but it is usually within 1 hour, preferably within 30 minutes, more preferably within 15 minutes. There are no particular restrictions on the lower limit, and it is usually sufficient if the compound added in the preceding step is sufficiently dissolved or dispersed.
[0046] One embodiment of this manufacturing method is as follows: a method for producing Zn-MOF comprising a zinc compound solution preparation step of preparing a solution of the zinc compound, and an addition step of adding a triazole compound and an oxalate compound, which may have substituents, to the zinc compound solution. More specifically, the method involves preparing a zinc compound solution by adding the zinc compound to the solvent and mixing it, and then adding a triazole compound and an oxalate compound (which may have substituents) and a carboxylic acid compound (which is not a zinc compound) to this zinc compound solution. Here, the order in which the triazole compound and oxalate compound and the carboxylic acid compound (which may have substituents) are added is not limited; the three compounds may be added simultaneously or sequentially. Furthermore, in the zinc compound solution preparation step, when adding triazole compounds, oxalate compounds, and non-zinc carboxylic acid compounds, which may have substituents, to the zinc compound solution, they may be added directly. Alternatively, the triazole compounds, oxalate compounds, and non-zinc carboxylic acid compounds may be dissolved or dispersed in another solvent before being added. The type of solvent used in this case is the same as that described above, and the ratio of the mixed solvents is also the same. Here, the solvent mixing ratio refers to the ratio of the total amount of solvent at the time all compounds have been added.
[0047] When reacting in the reaction solution, the total concentration of all raw materials (zinc compound, oxalate compound, optionally substituted triazole compound, and carboxylic acid compound) is usually 0.1 mol / L or higher, preferably 0.3 mol / L or higher, more preferably 0.5 mol / L or higher, and usually 10 mol / L or lower, preferably 5 mol / L or lower, more preferably 3 mol / L or lower. If the concentration is above the lower limit, the reaction proceeds sufficiently, and the yield of Zn-MOF can be increased. On the other hand, if the concentration is below the upper limit, it is advantageous in that the viscosity range allows for sufficient stirring, thus increasing the yield. When the reaction is carried out in the reaction solution, the concentration of the zinc compound is usually 0.01 mol / L or higher, preferably 0.1 mol / L or higher, more preferably 0.15 mol / L or higher, and even more preferably 0.3 mol / L or higher, and usually 5 mol / L or lower, preferably 2 mol / L or lower, and more preferably 1 mol / L or lower. When the concentration of the zinc compound is within the above range, the reaction proceeds sufficiently and the yield of Zn-MOF can be increased. Note that the concentration of the zinc compound mentioned above may be replaced with the concentration of the carboxylic acid compound when zinc carboxylate is used as the zinc compound. When the reaction is carried out in the reaction solution, the concentration of the carboxylic acid compound is usually 0.05 mol / L or higher, preferably 0.1 mol / L or higher, more preferably 0.2 mol / L or higher, and usually 5 mol / L or lower, preferably 3 mol / L or lower, more preferably 2 mol / L or lower. When the concentration of the carboxylic acid compound is within the above range, the reaction proceeds sufficiently and the yield of Zn-MOF can be increased. When the reaction is carried out in the reaction solution, the concentration of the triazole compound, which may have substituents, is usually 0.05 mol / L or higher, preferably 0.15 mol / L or higher, more preferably 0.3 mol / L or higher, and usually 10 mol / L or lower, preferably 5 mol / L or lower, more preferably 2 mol / L or lower. When the concentration of the triazole compound, which may have substituents, is within the above range, the reaction proceeds sufficiently and the yield of Zn-MOF can be increased. When the reaction is carried out in the reaction solution, the concentration of the oxalate compound is usually 0.01 mol / L or higher, preferably 0.04 mol / L or higher, more preferably 0.08 mol / L or higher, and usually 2.5 mol / L or lower, preferably 1.2 mol / L or lower, more preferably 0.6 mol / L or lower. When the concentration of the oxalate compound is within the above range, the reaction proceeds sufficiently, and the yield of Zn-MOF can be increased.
[0048] <Organic-inorganic hybrid membrane> This disclosure provides an organic-inorganic hybrid membrane (Mixed Matrix Membrane) formed from a composition comprising a metal-organic framework according to one embodiment and a resin. The organic-inorganic hybrid membrane formed from the composition of this disclosure may also be referred to as MMM. The lid film may include, in addition to the film formed from the composition of this disclosure, a base layer and a protective layer as described later. Furthermore, the organic-inorganic hybrid film can be used after being formed on a substrate as described later. The substrate and the organic-inorganic hybrid film together are sometimes referred to as an organic-inorganic hybrid film composite. The organic-inorganic hybrid membranes and organic-inorganic hybrid membrane composites of this disclosure can be suitably used as separation membranes, particularly for gas separation, especially for the separation of carbon dioxide gas, hydrogen, and helium.
[0049] The MOF content in the organic-inorganic hybrid film of this disclosure is typically 10% by mass or more, more preferably 15% by mass or more, even more preferably 20% by mass or more, particularly preferably 30% by mass or more, even more preferably 40% by mass or more, and most preferably 45% by mass or more. On the other hand, it is typically 95% by mass or less, preferably 90% by mass or less, more preferably 85% by mass or less, and even more preferably 80% by mass or less. When the MOF content is within the above range, the film tends to have excellent flexibility and processability.
[0050] (resin) The resin included in the composition for obtaining an organic-inorganic hybrid film is not particularly limited, but at least one selected from the group consisting of silicone rubber made from polyorganosiloxanes such as polyimide, polyamide, polysulfone, polyvinylpyrrolidone, polybenzimidazole, polybenzoxazole, polyoxyethylene, polyphenylene ether, polyether ketone, polyketone, tetrafluoroethylene amorphous polymer, macroporous polymer (PIM), polyether block amide, and polydimethylsiloxane (hereinafter sometimes referred to as PDMS), rubbers such as styrene-butadiene rubber, butadiene rubber, isoprene rubber, ethylene-propylene rubber, natural rubber, acrylic rubber, ethylene-vinyl oxide rubber, and polyolefins such as poly(4-methyl-1-pentine) is preferred.
[0051] The resin contained in the composition may be coordinately bonded to the metal ions of the MOF. When the resin is coordinated, it is preferable that the resin has at least one functional group selected from the group consisting of amino groups, imidazolium groups, carboxyl groups (-COOH), phenolic hydroxyl groups (-PhOH), thiol groups (-SH), sulfo groups (-SO3H), phosphonic acid groups (-PO3H2), and phosphate groups (-OPO3H2). Of these, carboxyl groups and imidazole groups are preferred because they readily coordinate with the metal ions of the MOF.
[0052] The resin contained in the composition may be chemically bonded to the MOF. If the resin is chemically bonded, it is preferable that the resin has at least one functional group selected from the group consisting of hydroxyl groups, epoxy groups, amino groups, isocyanate groups, cyano groups, acrylic groups, methacrylic groups, vinyl groups, thiol groups, carbonyl groups, carboxylic acid anhydrides, and derivatives thereof.
[0053] The weight-average molecular weight (Mw) of the resin contained in the composition is preferably high in terms of preventing penetration into the substrate and reducing the occurrence of defects when the composition of this disclosure is applied to the substrate, and on the other hand, it is preferable that it is lower in terms of being easily diluted with a solvent and having excellent film-forming properties. Therefore, the weight-average molecular weight is preferably 1,000 to 500,000, more preferably 1,500 to 100,000, and even more preferably 3,000 to 50,000.
[0054] For example, when gas separation is performed using the molecular sieving effect or adsorption selectivity of MOFs, it is preferable that the composition contains a high amount of MOF. Therefore, it is preferable that the glass transition temperature (Tg) of the resin contained in the composition of this disclosure is low in terms of easily incorporating a high concentration of MOFs and having excellent film-forming properties and flexibility.
[0055] In other words, when the glass transition temperature of the resin is low, even if the MOF content is high when using a membrane made of the composition of this disclosure for gas separation, the flexibility of the matrix resin prevents gaps from forming between the MOF and the resin, resulting in a membrane that exhibits high permeability and separation performance. Furthermore, when the glass transition temperature of the resin is low, even if strain occurs at the interface between the matrix resin and the MOF under high pressure conditions or prolonged use, the flexibility of the resin can absorb it, making it less likely for gaps to form. Moreover, because the resin is flexible, even when the membrane is processed into a spiral or other shape to form modules, no gaps form between the matrix resin and the MOF, resulting in good membrane performance. Therefore, the glass transition temperature of the resin is preferably 15°C or lower, more preferably 0°C or lower, even more preferably -20°C or lower, particularly preferably -50°C or lower, even more preferably -70°C or lower, and most preferably -100°C or lower. The lower limit of the glass transition temperature of the resin is not particularly limited, but -250°C is preferred, and -200°C is more preferred. The method for measuring the glass transition temperature is the same as that described in the examples.
[0056] The CO2 gas permeability coefficient of the resin contained in the composition at 35°C is preferably high, as this tends to result in a higher gas permeability coefficient when the composition of this disclosure is used as a film. Specifically, the gas permeability coefficient of the resin is preferably 200 Barrer or more, more preferably 500 Barrer or more, even more preferably 1000 Barrer or more, particularly preferably 1500 Barrer or more, and most preferably 2000 Barrer or more. Here, the CO2 permeability coefficient at 35°C is the value obtained by measuring the CO2 permeability coefficient of a membrane made solely of resin (hereinafter sometimes referred to as "resin membrane") at a differential pressure of 0.1 MPa. The permeability coefficient, separation coefficient, and transmittance of the resin are the values obtained by preparing a resin membrane and measuring it at a differential pressure of 0.1 MPa at 35°C using the same method as the measurement method for the permeability coefficient, separation coefficient, and transmittance of the membrane described later in this disclosure.
[0057] Resins having a desirable glass transition temperature and CO2 gas permeability coefficient include polyether block amides, silicone rubbers made from polyorganosiloxanes such as PDMS, styrene-butadiene rubber, butadiene rubber, isoprene rubber, ethylene-propylene rubber, natural rubber, acrylic rubber, ethylene-vinyl oxide rubber, and polyolefins such as poly(4-methyl-1-pentine). More preferably, are silicone rubbers made from polyether block amides, PDMS, and other polyorganosiloxanes, styrene-butadiene rubber, butadiene rubber, isoprene rubber, ethylene-propylene rubber, natural rubber, acrylic rubber, and ethylene-vinyl oxide rubber. Silicone rubber made from polyorganosiloxanes such as PDMS is particularly preferred. By fabricating a membrane using a composition containing these resins, a gas separation membrane with excellent gas permeability and separation performance can be obtained.
[0058] The preferred silicone rubbers mentioned above are not particularly limited, but are preferably polyorganosiloxanes having a siloxane skeleton represented by the following formula (3), or commercially available silicone rubber precursors that have been crosslinked and cured. Examples of commercially available silicone rubber precursors include SILPOT™ 184 Silicone Elastomer Base (manufactured by Dow-Toray Industries, Inc.).
[0059] [ka]
[0060] In equation (3), n is an integer greater than or equal to 2, and R 11 and R 12 Each of these groups may independently be an alkyl group such as a methyl group or an ethyl group; a cycloalkyl group such as a cyclohexyl group; a polyether group; an alkenyl group such as a vinyl group or an allyl group; an aryl group such as a phenyl group or a fluorenyl group; a heteroalkyl group such as a fluoroalkyl group; or a saturated or unsaturated alicyclic group containing a heteroelement such as an oxyranyl group or an oxetanyl group. These groups may also have substituents that undergo condensation reactions, such as a hydrogen atom, a hydroxyl group, a halogen atom, an alkoxy group, a ketoxime group, an acetoxy group, or an aminooxy group, or substituents such as an amino group, a carboxyl group, a carbinol group, or an epoxy group. Furthermore, the substitution form of the polyorganosiloxane in formula (3) is the R of the side chain. 11 , R 12 It may be substituted, both ends may be substituted, or both ends and the side chain may be substituted. 11 and R 12 They may be the same or different from each other, and some of the R's in polyorganosiloxanes 11 , R 12 Only the substitution is acceptable.
[0061] In terms of polymerizing or condensing the polyorganosiloxane of formula (3) by a crosslinking reaction to produce silicone rubber, the polyorganosiloxane of formula (3) preferably has crosslinkable groups such as vinyl groups, alkenyl groups, oxetanyl groups, silicon-hydrogen bonds, hydroxyl groups, halogen atoms, alkylosyl groups, ketoxime groups, acetoxy groups, aminooxy groups, and other substituents that undergo condensation reactions. It is particularly preferable that it has alkenyl groups in order to utilize addition reactions.
[0062] As commercially available polyorganosiloxanes having a hydroxyl group at the end of formula (3), Aldrich's poly(dimethylsiloxane), hydroxy-terminated (viscosity 2550-3570 cSt), poly(dimethylsiloxane), hydroxy-terminated (viscosity 18,000-22,000), and poly(dimethylsiloxane), hydroxy-terminated (viscosity ~50,000 cSt) are preferred, and the hydroxy-terminated (viscosi A value of ty (18,000-22,000) is particularly preferred.
[0063] In terms of polymerizing or condensing the polyorganosiloxane of formula (3) by a crosslinking reaction to produce silicone rubber, the polyorganosiloxane of formula (3) preferably has crosslinkable groups such as vinyl groups, alkenyl groups, silicon-hydrogen bonds, hydroxyl groups, oxetanyl groups, alkoxy groups, ketoxime groups, acetoxy groups, aminooxy groups, and other substituents that undergo condensation reactions. It is particularly preferable that it has silicon-hydrogen bonds that can be used for addition reactions, alkenyl groups, or hydroxyl groups that can be used for condensation reactions.
[0064] The mechanism of the crosslinking reaction when the above-mentioned polyorganosiloxane is crosslinked and cured to form silicone rubber is not particularly limited, and conventionally known curing reactions using organic peroxides, condensation reactions, addition reactions, ultraviolet light, radiation, or electron beam irradiation can be used. From the viewpoint of productivity, types that cure by addition reactions, condensation reactions, ultraviolet light, radiation, or electron beam irradiation are preferred because they are easy to mix with MOFs and can be stored stably in the atmosphere after mixing with MOFs. Addition reactions or condensation reactions are particularly preferred because they do not require atmospheric control other than temperature and humidity during curing, making them simple.
[0065] When using polyorganosiloxanes, the weight-average molecular weight (Mw) is typically 5,000 or more, preferably 10,000 or more, more preferably 20,000 or more, and even more preferably 25,000 or more, while on the other hand, it is typically 100,000 or less. Because the weight-average molecular weight of the polyorganosiloxane contained in the composition of this disclosure is within the above range, mixing with MOFs becomes easier, the MOF content in the composition of this disclosure can be increased, and film-forming properties are also excellent. Examples of polyorganosiloxanes that can be suitably used in this disclosure include SILPOT™184 manufactured by Dow Toray Ltd., ELASTOSIL RT601 manufactured by Asahi Kasei Wacker Silicone Co., Ltd., and TSE382-C manufactured by Momentive Performance Materials Japan LLC.
[0066] (base material) The organic-inorganic hybrid film of this disclosure may be used alone, or it may be laminated on a substrate to form an organic-inorganic hybrid film composite. Laminating the organic-inorganic hybrid film formed with the composition of this disclosure onto a substrate is preferable because it increases the durability and strength of the organic-inorganic hybrid film compared to the case of the organic-inorganic hybrid film alone, thereby allowing the organic-inorganic hybrid film to be made thinner.
[0067] As a substrate, a porous substrate is preferred from the viewpoint of excellent permeability performance of the organic-inorganic hybrid membrane of this disclosure. The shape of the porous substrate is not particularly limited, but examples include porous membranes, porous hollow fiber membranes, and nonwoven fabrics, and porous hollow fiber membranes are preferred because they can increase the membrane area per unit volume. The pore size of the porous substrate is typically 100 μm or less, preferably 50 μm or less, more preferably 10 μm or less, even more preferably 5 μm or less, particularly preferably 1 μm or less, and most preferably 0.5 μm or less. On the other hand, it is typically 0.01 μm or more, preferably 0.1 μm or more, and more preferably 0.2 μm or more. When the pore size of the substrate is within the above range, gases can easily permeate the film, and it exhibits excellent strength. The porous structure of the substrate may be uniform or asymmetrical, having a rough layer beneath a dense surface layer. However, an asymmetrical structure is preferable because it makes it easier to reduce resistance during gas permeation.
[0068] The thickness of the porous substrate is preferably thick in terms of film strength, but preferably thin in terms of gas permeability. Therefore, the thickness of the porous substrate is usually 10 μm or more, preferably 30 μm or more, more preferably 50 μm or more, even more preferably 70 μm or more, and particularly preferably 100 μm or more, while on the other hand, it is usually 2 mm or less, preferably 1 mm or less, more preferably 500 μm or less, even more preferably 200 μm or less, and particularly preferably 150 μm or less.
[0069] The material of the porous substrate is not particularly limited, but is usually a polymer, preferably at least one selected from the group consisting of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyethersulfone (PES), polysulfone (PSU), cellulose acetate (CA), polyethylene (PE), polypropylene (PP), polycarbonate (PC), polyimide (PI), polyacrylonitrile (PAN), and polyamide, more preferably at least one selected from the group consisting of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyethersulfone (PES), cellulose acetate (CA), and polyacrylonitrile (PAN), and particularly preferably polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE). When the porous substrate is made of these materials, it has excellent flexibility and strength, and there are fewer restrictions on the lamination method and conditions when laminating a film made of the composition of this disclosure. Therefore, a film with excellent strength, flexibility, and processability can be obtained.
[0070] (base layer) The substrate may have a multilayer structure. If the substrate has a multilayer structure, there may be an additional underlayer (=gutter layer) between the film made of the composition of this disclosure and the substrate of the preferred material described above. The material of the substrate is not particularly limited, but examples include silicone resin, polyethersulfone (PES), polysulfone (PSU), polyethylene oxide (PEO), and poly[1-(trimethylsilyl)-1-propyne] (PTMSP). Of these, silicone resin and polyethylene oxide (PEO) are preferred, and silicone resin is particularly preferred, because they have high solvent resistance and allow for fewer restrictions on the film formation method when forming a film on the substrate. The thickness of the underlayer is preferably thin in order to reduce the permeation resistance as a separation membrane. Specifically, it is usually 1 nm or more, preferably 10 nm or more, and on the other hand, it is usually 3 μm or less, preferably 1.5 μm or less, more preferably 1 μm or less, and even more preferably 500 nm or less.
[0071] (protective layer) The organic-inorganic hybrid film of this disclosure may have a protective layer. The material of the protective layer is not particularly limited, but examples include silicone resin, poly[1-(trimethylsilyl)-1-propyne] (PTMSP), polyethersulfone (PES), polysulfone (PSU), polyethylene oxide (PEO), etc. Of these, silicone resin, poly[1-(trimethylsilyl)-1-propyne] (PTMSP), and polyethylene oxide (PEO) are preferred, with silicone resin being particularly preferred because it has high gas permeability and has little effect on the film made of the composition of this disclosure. When a protective layer is provided, it is preferable for the film to be thin in terms of gas permeability, but on the other hand, it is preferable for the film to be thick in terms of film strength and scratch resistance. Therefore, the thickness of the protective layer is usually 1 nm or more, preferably 10 nm or more, more preferably 100 nm or more, and on the other hand, it is usually 100 μm or less, preferably 10 μm or less, and more preferably 1 μm or less.
[0072] (Thickness of organic-inorganic hybrid film) The thickness of the organic-inorganic hybrid film disclosed herein is preferably thin in terms of excellent gas permeability and flexibility, while on the other hand, it is preferable that it is thick in terms of excellent water resistance, hydrothermal stability, flexibility and processability, less prone to cracking and pinholes, and easier to modularize. Therefore, when using only the organic-inorganic hybrid film of this disclosure, a thickness of 1 μm or more is usually preferred, preferably 5 μm or more, and more preferably 10 μm or more. On the other hand, a thickness of 1,000 μm or less is usually preferred, preferably 500 μm or less, more preferably 300 μm or less, even more preferably 250 μm or less, and particularly preferably 200 μm or less.
[0073] Furthermore, when a layer other than the organic-inorganic hybrid film is present, the film thickness is usually 0.05 μm or more, preferably 0.1 μm or more, more preferably 1 μm or more, and even more preferably 2 μm or more. On the other hand, it is usually 100 μm or less, preferably 50 μm or less, more preferably 30 μm or less, even more preferably 10 μm or less, and particularly preferably 5 μm or less. Furthermore, when the organic-inorganic hybrid film of this disclosure is formed on a porous substrate or a porous protective film, the combined thickness of these substrates and protective layers is usually 0.05 μm or more, preferably 0.1 μm or more, more preferably 1 μm or more, and even more preferably 2 μm or more. On the other hand, it is usually 100 μm or less, preferably 50 μm or less, more preferably 30 μm or less, even more preferably 10 μm or less, and particularly preferably 5 μm or less.
[0074] (Bending test) The organic-inorganic hybrid film of this disclosure exhibits excellent flexibility. Specifically, it is preferable that the film of this disclosure has a gas permeability coefficient, gas permeability, and separation coefficient after a bending test (a test in which the film is bent 180° along a curved surface with a bending radius (radius of curvature) of 5 mm and then straightened) that are within 10% of those before the bending test. Here, the bending radius (radius of curvature) when performing the above bending test is preferably 4 mm or less, more preferably 3 mm or less, and even more preferably 2 mm or less, while on the other hand, it is usually 0.1 mm or more, preferably 0.5 mm or more, and more preferably 1 mm or more. The film disclosed herein exhibits excellent flexibility, allowing it to be bent for use. It also offers excellent processability, making it easy to process into spiral or pleated modules without cracking or creating pinholes. Furthermore, when forming the film into a hollow fiber shape, it is easier to do so without cracking or creating pinholes.
[0075] (Method for manufacturing organic-inorganic hybrid films) The film of this disclosure can be manufactured by known resin film manufacturing methods. For example, the MOF may be dissolved in a solvent and mixed with a resin, or mixed with a resin and then manufactured. In the case of a resin that requires a curing process, the film may be manufactured by mixing with the resin before curing and then curing. Specifically, after drying the MOF, it is mixed with a resin dissolved in a solvent or a solvent-free resin raw material, dispersed, and then, if a resin requiring a curing agent is used, the curing agent is added and mixed to further disperse the MOF.
[0076] Methods for dispersing MOF in resin include conventional stirring and kneading, as well as methods using ultrasonic crushing and dispersion, and rotary / revolving mixers. The material is preferably obtained by casting a slurry of MOF, resin or resin raw materials, and other optional components such as curing agents with a solvent onto a release-resistant petri dish or film made of Teflon® or polyimide. The metal-organic framework of this disclosure is in a flat (also called plate) form, which allows for a thin film thickness of the organic-inorganic hybrid film while providing high gas separation capability to the organic-inorganic hybrid film. Therefore, when casting to form a film, it is desirable to apply shear using a blade, applicator, or bar coater, which allows the flat metal-organic framework to be layered. Accordingly, it is preferable to apply a slurry of MOF, resin or resin raw materials, and other optional components such as curing agents with a solvent onto a release-resistant film using a blade, applicator, or bar coater. In particular, application with a blade or applicator is preferred. The film of this disclosure can be obtained by coating a release film, then placing it in a dryer to remove the solvent and curing it at a predetermined temperature and time, or by curing the resin in an inert oven under a nitrogen stream while evaporating the solvent. Here, the temperature and vacuum level of the dryer are set appropriately according to the solvent used. The curing temperature and curing time should also be set under conditions suitable for the resin used.
[0077] When a porous flat film is used as the substrate, the film according to the disclosure can be manufactured by forming a film of the composition according to the disclosure to a constant thickness on the substrate using a blade. Here, the composition according to the disclosure may be prepared in advance on the porous substrate, and then a protective layer may be formed on top of it. Alternatively, the film may be formed on a substrate having a base layer. The method for forming the protective layer and the base layer may be carried out in accordance with the method for manufacturing the organic-inorganic hybrid film according to the disclosure. Alternatively, the above-mentioned mixed slurry can be supported on the substrate by methods such as impregnation, suction, or pressurization to form the film. After that, the organic-inorganic hybrid film can be obtained by removing the solvent using a dryer and then curing it, or by curing the resin in an inert oven while volatilizing the solvent under a nitrogen stream.
[0078] When porous hollow fibers are used as the substrate, the composition of this disclosure can be supported on the substrate by methods such as impregnation, suction, or pressurization to form a film.
[0079] When using silicone rubber cured from polyorganosiloxane as the resin, the MOF is usually mixed with the polyorganosiloxane before curing. The means for curing the curable polyorganosiloxane are not particularly limited, and conventionally known methods can be employed. From the viewpoint of productivity, curing by a curing method that allows for stable mixing of MOFs and storage after MOF mixing in the atmosphere is preferred. In this respect, types that cure by addition reaction, ultraviolet light, radiation, or electron beam irradiation are preferred, and the use of an addition reaction is particularly preferred because it does not require atmospheric control during curing and is simple.
[0080] Before mixing the resin with the MOF, it is preferable to dry the MOF. When heat-drying the MOF, the temperature is usually 100°C or higher, preferably 120°C or higher, and on the other hand, usually 200°C or lower, preferably 170°C or lower. The drying time is usually 3 hours or more, preferably 5 hours or more, more preferably 8 hours or more, and even more preferably 12 hours or more, and on the other hand, usually 48 hours or less, preferably 30 hours or less, and more preferably 20 hours or less. When the drying temperature and time are within these ranges, it is easy to sufficiently remove moisture from the MOF in a short time.
[0081] The solvent used for film formation is not particularly limited as long as it is a solvent in which the resin or resin raw material is soluble. For example, toluene, hexane, ethyl acetate, methyl ethyl ketone, N-methylpyrrolidone, etc., can be used. A solvent that provides good dispersibility of the MOF is preferred. Since most resins or resin raw materials are hydrophobic, while the MOF surface is hydrophilic, a solvent with moderate polarity, such as ethyl acetate or methyl ethyl ketone, is preferred.
[0082] The amount of solvent varies depending on the amount of MOF and the type of resin, but it is preferable to adjust the amount of solvent so that the viscosity is suitable for film formation, depending on the film formation method.
[0083] In film formation, it is preferable to cure the resin while applying pressure. By curing the resin under pressure, it is easier to produce a void-free film even with a large amount of MOF.
[0084] The pressurization method is not particularly limited, but it is preferable to apply pressure to the film using a hot press or vacuum hot press while heating and curing it. The pressure is typically 1 MPa or higher, preferably 2 MPa or higher, more preferably 3 MPa or higher, even more preferably 4 MPa or higher, and particularly preferably 5 MPa or higher. On the other hand, it is typically 30 MPa or lower, preferably 20 MPa or lower, more preferably 10 MPa or lower, and even more preferably 8 MPa or lower. When the pressure is within the above range, it is possible to obtain a film with a high amount of MOF without destroying the pores of the MOF in the film, without gaps between MOFs or between MOFs and the resin. The heating temperature and heating time can be appropriately determined according to the curing conditions of the resin used, but the heating time under pressure is usually 1 minute or more, preferably 5 minutes or more, and more preferably 10 minutes or more, while the heating time is usually 2 hours or less, preferably 1 hour or less. Heating within this range makes it easy to efficiently produce a film without voids.
[0085] <Gas Separation and Concentration Methods> The organic-inorganic hybrid membrane of this disclosure can separate and concentrate gas mixtures and can be used as a gas separation membrane. According to the gas separation membrane of this disclosure, highly permeable gases can be separated from a gas mixture. Examples of gas mixtures separated by the separation membrane of this disclosure include those containing at least one component selected from carbon dioxide, hydrogen, oxygen, nitrogen, methane, ethane, ethylene, propane, propylene, n-butane, isobutane, 1-butene, 2-butene, isobutene, sulfur hexafluoride, helium, carbon monoxide, nitric oxide, and water vapor. Of these, it is suitable for separating at least one gas selected from the group consisting of carbon dioxide, hydrogen, oxygen, nitrogen, methane, ethane, ethylene, propane, propylene, butane, butene, sulfur hexafluoride, helium, carbon monoxide, nitric oxide, and water vapor from the gas mixture. Of the mixed gas components described above, gas components with high permeance (hereinafter sometimes referred to as "gas permeability") are separated and concentrated by permeating through the membrane of this disclosure, while gas components with low gas permeability are concentrated on the supply gas side.
[0086] As the mixed gas, a gas containing at least two of the above-mentioned components is more preferable. In this case, a combination of a component with high gas permeability and a component with low gas permeability is preferable.
[0087] For gas separation applications, it is preferable to use it for the separation and concentration of CO2, H2, He, oxygen, and nitrogen, and is particularly preferable to use it for the separation and concentration of CO2, H2, and He.
[0088] CO2 separation and concentration methods include the removal of carbon dioxide from natural gas (CO2, CH4 mixture), CO2 recovery from landfill gas (CO2, CH4 mixture), CO2 recovery from artificial fermentation gas (CO2, CH4 mixture), and CO2 recovery from combustion exhaust gas (CO2, N2 mixture) from thermal power plants, etc. Examples of He separation and concentration include the separation and concentration of He from natural gas (a mixture of He, CO2, and CH4) and the separation and concentration of spent He (a mixture of He, N2, and O2).
[0089] Examples of hydrogen separation and concentration include hydrogen recovery in the petroleum refining industry, hydrogen recovery and purification (H2, CO, CO2, hydrocarbon mixtures) in various reaction processes in the chemical industry, and the production of high-purity hydrogen for fuel cells. Hydrogen for fuel cells is obtained by the steam reforming reaction of methane, and requires the separation of hydrogen from a mixed gas of hydrogen, carbon monoxide, methane, and water.
[0090] In addition, oxygen separation and concentration can be used to produce oxygen-enriched gas from air (for medical and combustion purposes, etc.), and it is also suitably used to produce nitrogen-enriched gas from air through nitrogen separation and concentration (for explosion prevention, oxidation prevention, etc.). A known method can be used for separating the gases. For example, a partial pressure difference can be created between the gas supply side and the gas permeate side of the membrane, allowing the gas that is more easily permeated from the mixed gas on the supply side to permeate to the permeate side. At this time, the mixed gas on the gas supply side may be pressurized, the permeate side may be depressurized using a vacuum pump or the like, or both may be used.
[0091] In a gas separation method that applies a pressure difference between the gas supply side and the permeate side, it is preferable to use an appropriately optimal pressure difference, which is usually 0.01 MPa or more, preferably 0.05 MPa or more, more preferably 0.08 MPa or more, and even more preferably 0.1 MPa or more. On the other hand, it is usually 20 MPa or less, preferably 10 MPa or less, more preferably 5 MPa or less, even more preferably 1 MPa or less, particularly preferably 0.5 MPa or less, and most preferably 0.2 MPa or less.
[0092] There are no particular restrictions on the pressure on the gas supply side in the gas separation method, but it is preferable to use an appropriate and optimal supply pressure. Typically, it is 0.05 MPaG or higher, preferably 0.1 MPaG or higher, typically 20 MPaG or lower, preferably 10 MPaG or lower, more preferably 5 MPaG or lower, even more preferably 0.9 MPaG or lower, particularly preferably 0.5 MPaG or lower, and most preferably 0.2 MPaG or lower. It is desirable to be able to obtain a large differential pressure, but high pressures increase the cost of equipment that can withstand high pressure and compliance with relevant laws and regulations.
[0093] In the gas separation and concentration method using the separation membrane of this disclosure, a sweep gas may be used. The sweep gas method involves flowing some gas through the permeate side and recovering the gas that has permeated the membrane. The sweep gas pressure is usually atmospheric pressure, but there are no particular restrictions. It is usually 10 MPaG or less, preferably 5 MPaG or less, more preferably 1 MPaG or less, even more preferably 0.5 MPaG or less, particularly preferably 0.1 MPaG or less, and most preferably 0.05 MPaG or less, with the lower limit usually being 0.0 MPaG.
[0094] <Adsorbent material> According to this disclosure, a carbon dioxide adsorbent containing the MOF of this disclosure (hereinafter sometimes referred to as "the CO2 adsorbent of this disclosure" or simply "the CO2 adsorbent") can be provided. That is, the MOF of this disclosure can be suitably used as a CO2 adsorbent. Because the CO2 adsorbent of this disclosure contains the MOF of this disclosure, it can sufficiently adsorb carbon dioxide and has high selectivity for carbon dioxide adsorption compared to nitrogen adsorption. Therefore, it can be suitably used, for example, for the selective removal of carbon dioxide from exhaust gases from power plants, factories, and automobiles.
[0095] The CO2 adsorbent described herein may be activated before use. A method known in the art may be used to activate the adsorbent. In a specific embodiment, the MOF contained in the adsorbent is activated by heating under reduced pressure. Activation allows for the removal of the adsorbed substance. More specifically, reduced pressure, for example, 10 -3 mbar or less, preferably 10 -6 The MOF of this disclosure contained in the adsorbent can be activated by heating it to a temperature of approximately 100 to 150°C in mbar. In another embodiment, during the two-step heating process, under reduced pressure (preferably 10 -6 The MOFs contained in the adsorbent can be activated by a first step of heating at 60°C for 2 hours at a rate of mbar, followed by a second step of heating at 100°C for 12 hours. Activation may also be carried out by heating at a controlled rate (e.g., 1°C / min). For example, the MOF can be activated by heating at 60°C at 1°C / min for 2 hours, followed by heating at a heating rate of 1°C / min to 100°C for 12 hours. In another embodiment, the MOFs contained in the adsorbent may be treated or washed with an organic solvent such as acetone before heating under reduced pressure.
[0096] The CO2 adsorbent of this disclosure is not particularly limited in its composition, as long as it contains the MOF of this disclosure. There are no particular restrictions on the form in which the adsorbent of this disclosure is used; for example, the adsorbent may be used as is in powder form, or it may be supported on various substrates (e.g., aluminum honeycomb), or it may be molded into various shapes as needed.
[0097] The adsorbent of this disclosure may contain a binder in addition to the MOF. Both inorganic and organic binders can be used. Examples of inorganic binders include silica binders. Examples of organic binders that can be used include polysulfone, polylactic acid, polyethylene glycol, and polyvinylpyrrolidone.
[0098] The adsorbent of this disclosure may be placed, for example, on the inlet and outlet sides of a processing vessel or on a filter placed between them. As the filter, for example, a quartz filter can be used. When the adsorbent of this disclosure is used to remove carbon dioxide from exhaust gas from a power plant, factory, or automobile, exhaust gas can be introduced from an upper line, impurities can be removed by a filter, and then carbon dioxide can be selectively adsorbed and removed by the MOF of this disclosure, and nitrogen-enriched gas can be extracted from a lower line.
[0099] (Separation method) The gas separation method using the CO2 adsorbent of this disclosure allows for the separation of one or more gases selected from the group consisting of helium, hydrogen, carbon dioxide, nitrogen, and methane from a mixed gas containing at least one gas selected from the group consisting of carbon dioxide, hydrogen, oxygen, nitrogen, methane, ethane, ethylene, propane, propylene, butane, butene, sulfur fluoride, helium, carbon monoxide, nitric oxide, and water vapor, using the adsorbent of this disclosure. In this embodiment, it is preferable to separate carbon dioxide and / or nitrogen from one or more gases selected from the group consisting of nitrogen, carbon dioxide, and hydrocarbons. Examples of hydrocarbons are not particularly limited, but include methane, ethane, ethylene, propane, propylene, 1-butene, 2-butene, 2-methylpropene, dimethyl ether, acetylene, etc.
[0100] There are no particular limitations on the applications of the CO2 adsorbent disclosed herein. For example, it can be used as a CO2 adsorbent for adsorbing, separating, and recovering CO2 from exhaust gases from power plants and factories (where the proportion of CO2 in the exhaust gas is generally around 5-16% by volume, the exhaust gas temperature is generally around 50-75°C, and the pressure is around 100kPa) and from exhaust gases from automobiles (where the proportion of CO2 in the exhaust gas is generally around 10% by volume, the exhaust gas temperature is generally around 70-90°C, and the pressure is around 100kPa).
[0101] This disclosure is not limited to the embodiments described above, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of this disclosure. [Examples]
[0102] One embodiment of this disclosure is described below. (1) Powder X-ray diffraction (XRD) measurement method XRD measurements of MOFs were performed under the following conditions. Device: RIGAKU MiniFlex600 X-ray source: Cu-Kα ray Output settings: 40kV·15mA Divergence slit: 1.25° Incident solar slit: 2.5° Solar slit on the light-receiving side: 2.5° X-ray extraction angle: 6° Ni filter: 0.015mm thick Diffraction peak position: 2θ (diffraction angle) Measurement range: 2θ = 3~40° Scan speed: 5° (2θ / min)
[0103] (2) Single-component gas permeation test The single-component gas permeation test was performed using the constant volume / valuable pressure method with the apparatus schematically shown in Figure 1. The permeation side of the membrane (the lower side of membrane 1 in Figure 1) was reduced to 13 Pa (absolute pressure) or less, and gas was supplied at 35 kPa (G). The permeation coefficient was determined from the rate of pressure increase on the permeation side when the differential pressure between the supply side and the permeation side of the membrane was 0.1 MPa. The temperature of the constant temperature bath 16 was set to 35°C, and the permeation coefficient of the membrane at 35°C was determined. The ideal separation coefficient αA / B was determined from the ratio of the permeation coefficient of gas A to the permeation coefficient of gas B. Expressed as an equation, the ideal separation coefficient αA / B = permeation coefficient of gas A / permeation coefficient of gas B.
[0104] Gas was supplied from gas cylinder 18, and the manual valve 17 and valve 13 on the secondary side of the mass flow controller 5 were opened to supply gas through the mass flow controller 5. After filling the supply gas insulation gas reservoir 3 with 35 kPa (G) of gas to be used for the permeation test, valve 12 was closed and valve 11 was opened to supply gas to the membrane. At this time, valve 14 was open and valve 15 was closed. To ensure that the supply gas pressure remained constant, a fixed amount of gas was supplied through the mass flow controller 5 with valve 13 open, and the pressure was kept constant by the exhaust valve 6.
[0105] The permeability coefficient was calculated from the pressure increase rate measured by pressure gauge 7 after it became steady, as well as the volume from the bottom of the membrane to valve 12, the thickness, and the membrane area. For the permeable gas reservoir 8, the internal volume was measured from the amount of water after filling it with water, and for the piping section, the volume was calculated from the pipe length and inner diameter, thereby pre-calculating the volume from the bottom of the membrane to valve 12. An absolute pressure transducer (MKS Baratron (registered trademark) 0-10 toll (626C11TBE)) was used as the pressure gauge.
[0106] The gases used were carbon dioxide (99.9% purity, manufactured by Toho Oxygen Industries Co., Ltd.), methane (99.999% purity, manufactured by Japan Fine Products Co., Ltd.), hydrogen (99.99% purity, manufactured by Showa Denko Gas Products Co., Ltd.), and helium (99.995% purity or higher, manufactured by Japan Helium Center Co., Ltd.).
[0107] (Pretreatment of organic-inorganic hybrid membranes) In the gas permeation test, the membrane 1, set in membrane module 2, was heated to over 80°C for 2 hours using a constant temperature bath while reducing the pressure on both the supply and permeation lines. After 2 hours, the temperature of the constant temperature bath was lowered to 35°C and held there for 1 hour to remove water and gas dissolved or adsorbed on the membrane.
[0108] (Measurement of film thickness of organic-inorganic hybrid films) In single-component gas permeation tests, the thickness of organic-inorganic hybrid membranes was measured using a high-precision digital length measuring instrument (Mitutoyo Corporation, Lightmatic VL-50S-B). Three points were selected evenly around the circumference: the center of the membrane and three points slightly inward from the edge. The average of these four points was calculated. The area of the portion through which the gas permeated was defined as the membrane area.
[0109] (3) Measurement of aspect ratio and average particle size Test specimens for evaluating the aspect ratio of the metal-organic framework were prepared as follows. First, a slurry was prepared by mixing the metal-organic framework with resin components such as a silicone rubber precursor or polyorganosiloxane, a curing agent, a crosslinking agent, and an optional component such as a dispersant, and a solvent, so that the weight of the metal-organic framework after solvent evaporation was 45% to 55% of the total composition weight, and the solid content concentration of the slurry was 40% to 50%. Next, the prepared slurry was coated onto a polyimide film substrate placed on a glass plate using a Baker-type applicator set with a gap width of 8 mil. After the coated slurry was air-dried overnight, the solvent was removed by heating in a vacuum dryer at 120°C for 2 hours. If necessary, additional heating was performed to cure the silicone rubber, and the polyimide film was peeled off to prepare an organic-inorganic hybrid film containing the metal-organic framework. The aspect ratio of the metal-organic framework was determined by observing the cross-section obtained by fracturing the fabricated organic-inorganic hybrid film after it had been sufficiently cooled with liquid nitrogen, and then analyzing the resulting image to determine the particle cross-section. First, a cross-section of the organic-inorganic hybrid film was imaged at 1000x magnification using a scanning electron microscope to obtain a 1280 pixel × 1024 pixel image. From the obtained scanning electron microscope image, the portion other than the film cross-section was removed. Using the Segment Anything Model (Meta, weight file download date June 8, 2023), a mask (particle region) was created from the entire image. Points per Side was set to 64, Crop n Layers to 3, and other parameters were set to their default values for particle detection. The VIT-b model was used as the image encoder. For the detected particles, image analysis was performed using the Open Source Computer Vision Library (OpenCV) version 4.6.0 to calculate the particle area and the width and height of the circumscribing rectangle that minimizes the area. The obtained values indicate a particle area of 4000 nm. 2Particles smaller than 4000nm are removed as noise. 2 For each of the particles mentioned above, the aspect ratio of the particles in this image was obtained by calculating the ratio of the particle's width to its height, using the smaller of the two values as the denominator, and then taking the arithmetic mean. Furthermore, the diameter of a circle with an area equal to the particle area (equivalent diameter) is calculated, and the particle area is 4000 nm. 2 The average particle size of the particles in this image was obtained by taking the arithmetic mean of the equivalent circle diameters of the particles described above. It is preferable that the number of particles in the image subject to the arithmetic mean be 200 or more, and usually 10,000 or less. Since the area and length obtained from the image analysis are in pixels, the length of one pixel was determined from the actual size obtained from the image size and scale bar, and the length and area in pixels were converted to actual length and area. From the obtained cross-section, the aspect ratios of three images with different fields of view were determined using the method described above, and the aspect ratio of this metal-organic framework was obtained by taking the arithmetic mean of the aspect ratios of the three images. From the obtained cross-section, the average grain size was determined using the method described above for three images with a different field of view, and the average grain size of this metal-organic framework was obtained by taking the arithmetic mean of the average grain sizes of the three images. (Method 1)
[0110] A second method for determining the aspect ratio and average grain size of metal-organic frameworks with greater accuracy is described. Since the first method may produce errors depending on the grain size and image size of the metal-organic framework, the second method is added as a more accurate evaluation criterion for determining the aspect ratio and average grain size. First, a cross-section of the organic-inorganic hybrid film was imaged at 2000x magnification using a scanning electron microscope to obtain an image with an actual length of 0.047 μm / pixel per pixel. The obtained scanning electron microscope image was then edited to remove non-particle areas so that the number of vertical pixels and horizontal pixels were in a 1:1 ratio. Using the Segment Anything Model (Meta, weight file download date May 12, 2025), particle detection was performed by dividing the entire image into a mask (particle region) using a method that sets Points per Side to 32 and Crop n Layers to 0, with other parameters set to their default values. The sam 1.0 vit base model was used as the image encoder, and information regarding particles at the edges of the image was excluded. Image analysis was performed on the detected particles using the Open Source Computer Vision Library (OpenCV) version 4.11.0 to output the particle area. The particle area and the width and height of the circumscribing rectangle that minimizes the area were calculated. The obtained values are for a particle area of 4000 nm. 2 Particles smaller than 4000nm are removed as noise. 2 For each of the particles mentioned above, the aspect ratio of the particles in this image was obtained by calculating the ratio of the particle's width to its height, using the smaller of the two values as the denominator, and then taking the arithmetic mean. Furthermore, the diameter of a circle with an area equal to the particle area (equivalent diameter) is calculated, and the particle area is 4000 nm. 2 The average particle size of the particles in this image was obtained by taking the arithmetic mean of the equivalent circular diameters of the above particles. The number of particles detected in the image was set to be between 50 and 2000. Since the area and length obtained from the image analysis are in pixels, the length of one pixel was determined from the actual size obtained from the image size and scale bar, and the length and area in pixels were converted to length and area in metric units. From the obtained cross-sections, the aspect ratio and average grain size were determined for three images with different fields of view using the method described above. The aspect ratio of the metal-organic framework was obtained by taking the arithmetic mean of the aspect ratios of the three images, and the average grain size of the metal-organic framework was obtained by taking the arithmetic mean of the average grain size of the three images (Second Method).
[0111] (4) Measurement of carbon dioxide adsorption The amount of carbon dioxide adsorbed was measured under the following conditions. (Pre-processing) Prior to measuring the amount of carbon dioxide nitrogen adsorbed, 50 mg of the target powder was packed into a measurement cell, and the measurement cell was heated and vacuum-degassed for 4 hours at 10 Pa and 225°C using a pretreatment device (BELPREP vacII, manufactured by Microtrac-Bel Co., Ltd.). (Measurement of adsorption amount) Using a constant-volume gas adsorption method with carbon dioxide as the adsorption gas, the adsorption isotherm at a temperature of 298 K was measured for the powder after pretreatment. For the measurement, a gas adsorption device (Belsorp max, manufactured by Microtrac-Bel Co., Ltd.) was used to measure the amount of carbon dioxide adsorbed at each equilibrium pressure from 0 kPa to 102 kPa.
[0112] (5) Method for measuring the glass transition temperature The glass transition temperature was measured using a differential scanning calorimeter (DSC). The glass transition temperature was measured using a DSC600 manufactured by Hitachi High-Tech Science Corporation. Approximately 10 mg of resin sample was placed in an aluminum sample container, crimped, and heated from room temperature to 150°C at a heating rate of 10°C / min under a nitrogen stream of 30 mL / min. After holding the temperature for 1 minute, it was rapidly cooled to -150°C at a setting of 100°C / min and held at that temperature for 35 minutes. Then, it was heated again from -150°C to 150°C at a rate of 10°C / min. The inflection point of the DSC data obtained during the second heating was defined as the glass transition temperature.
[0113] [Manufacturing of metal-organic frameworks] [Example 1] Solution 1-1, containing zinc acetate, was prepared by dissolving 16.3 mmol of zinc acetate dihydrate in an aqueous methanol solution (MeOH / H2O = 10:10 ml) and stirring with a stirrer for 5 minutes. Subsequently, 32.4 mmol of the ligand 1,2,4-triazole, 8.20 mmol of sodium oxalate, and 32.4 mmol of sodium formate were added to a separately prepared aqueous methanol solution (MeOH / H2O = 10:10 ml), dispersing by sonication for 5 minutes, and then stirring for 5 minutes. Next, solution 1-2 was added to solution 1-1 and stirred for 72 hours. After stirring, solid-liquid separation was performed by centrifugation at 6000 rpm for 6 minutes, and the obtained solid was washed with pure water. Subsequently, the solid was dried overnight in an oven at 100°C under atmospheric pressure, followed by vacuum drying overnight at 130°C to obtain the product (Zn-MOF). The results of the powder X-ray diffraction (XRD) measurements described above yielded the XRD pattern shown in Figure 2, confirming that it was a Zn-MOF. The Zn-MOF obtained in Example 1 will be referred to as MOF1. While the maximum peak of this Zn-MOF is usually the peak at 2θ=14.20°, corresponding to the (0,1,1) plane, in MOF1, the peak intensity at 2θ=10.72°, corresponding to the (1,0,0) plane, was 76% of the peak intensity at 2θ=14.20°. It can be confirmed that anisotropic crystals are obtained from this as well.
[0114] (1) CO2 adsorption amount For MOF1, the amount of carbon dioxide adsorbed was measured using the method described above. V = 3.4 mmol / g (P = 100.11 kPa) (298 K).
[0115] 0.120 g of MOF1 dried at 150°C for 3 hours was weighed, and 0.091 g of poly(dimethylsiloxane), (hydroxy-terminated silicone resin P-1, viscosity: 18,000-22,000 cSt, manufactured by Sigma-Aldrich Japan) was added. The mixture was stirred for 15 minutes using a foam remover (manufactured by Thinky Co., Ltd.), and then degassed for 1 minute. 0.244 g of hexane (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added, and the mixture was dispersed in an ultrasonic cleaner for 30 minutes. Then, 0.026 g of tetraethyl orthosilicate (manufactured by Tokyo Chemical Industry Co., Ltd.) and 0.0067 g of dibutyltin dilaurate (manufactured by Sigma-Aldrich Japan) were added, and the mixture was stirred at room temperature to prepare the mixture. The prepared mixture was stirred for 7 minutes, and an appropriate amount was taken onto a polyimide film placed on a glass plate. The mixture was then coated onto the film using a Baker-type applicator set to 8 mil at a speed of 50 mm / s. The coated mixture was sealed overnight and then dried in a vacuum dryer at 120°C for 2 hours. The film was peeled off the polyimide film to obtain an organic-inorganic hybrid film M-1 containing a metal-organic framework. The film thickness was 36 μm. The solid content of the mixed solution used for film formation was 46% by mass, and the Zn-MOF content in the organic-inorganic hybrid film M-1 was 49% by mass. Table 1 shows the results of measuring the permeability coefficient and ideal separation coefficient of various gases at 35°C for the organic-inorganic hybrid membrane M-1.
[0116] The aspect ratio of the particle cross-section of the metal-organic framework of Example 1 was determined using the organic-inorganic hybrid film M-1 and the evaluation method described above. The aspect ratio measured by the first method was 2.1, and the aspect ratio measured by the second method was also 2.1. Furthermore, the average particle size calculated by the first method was 1.3 μm, and the average particle size calculated by the second method was 2.2 μm.
[0117] [Example 2] Solution 2 was prepared by adding 4.07 mmol of zinc formate dihydrate to an aqueous methanol solution (MeOH / H2O = 4:16 ml) and stirring with a stirrer for 10 minutes. Next, 2.04 mmol of sodium oxalate was added to the prepared solution 2 and stirred with a stirrer for 5 minutes. Then, 8.14 mmol of 1,2,4-triazole was added to solution 2 with sodium oxalate and stirred for 72 hours. After stirring, solid-liquid separation was performed by centrifugation at 6000 rpm for 6 minutes, and the obtained solid was washed with pure water. The obtained solid was then dried overnight in an oven at 100°C under atmospheric pressure, and then dried overnight under vacuum at 130°C. This yielded the product (Zn-MOF). The results of the above powder X-ray diffraction (XRD) measurements confirmed that it is a Zn-MOF.
[0118] (1) CO2 adsorption amount For MOF2, the amount of carbon dioxide adsorbed was measured using the method described above. V = 3.5 mmol / g (P = 100.12 kPa) (298 K).
[0119] Figure 3 shows an SEM image of the metal-organic framework of Example 2. From the SEM image in Figure 3, it can be confirmed that the metal-organic framework of Example 2 has a plate-like particle shape. An organic-inorganic hybrid film M-2 containing a metal-organic framework was obtained in the same manner as in Example 1, except that the obtained MOF2 was used. The film thickness was 40 μm. The solid content concentration of the mixture used for film formation was 47% by mass, and the Zn-MOF content in the organic-inorganic hybrid film M-2 was 50% by mass. Table 1 shows the results of measuring the permeability coefficient and ideal separation coefficient of various gases at 35°C for the organic-inorganic hybrid membrane M-2.
[0120] The aspect ratio of the particle cross-section of the metal-organic framework of Example 2, measured using the organic-inorganic hybrid film M-2 according to the evaluation method described above, was 2.5 according to the first method and 2.1 according to the second method. The average particle size calculated by the first method was 1.5 μm, and the average particle size calculated by the second method was 2.3 μm.
[0121] [Comparative Example 1] Solution c1 was prepared by adding 16.3 mmol of zinc acetate dihydrate, 8.20 mmol of sodium oxalate, and 32.4 mmol of 1,2,4-triazole in that order to a methanol aqueous solution (MeOH / H2O = 20:20 ml) while stirring. After adding 1,2,4-triazole, stirring was continued for 1 hour. After stirring, solid-liquid separation was performed by centrifugation at 6000 rpm for 6 minutes, and the obtained solid was washed with pure water. The obtained solid was then dried overnight in an oven at 100°C under atmospheric pressure, and then dried overnight under vacuum at 130°C. This yielded the product (Zn-MOF). The XRD pattern shown in Figure 4 was obtained by powder X-ray diffraction (XRD) as described above, confirming that it was Zn-MOF. The Zn-MOF obtained in Comparative Example 1 is referred to as MOF3. Furthermore, the maximum peak in this Zn-MOF corresponds to the (0,1,1) plane at 2θ=13.92°, while the peak intensity at 2θ=10.72°, corresponding to the (1,0,0) plane, is 13% of the peak intensity at 2θ=13.92°, which is different from MOF1 and MOF2.
[0122] An organic-inorganic hybrid film M-3 containing a metal-organic framework was obtained in the same manner as in Example 1, except that the obtained MOF3 was used. The film thickness was 142 μm. The solid content concentration of the mixture used for film formation was 41% by mass, and the Zn-MOF content in the organic-inorganic hybrid film M-3 was 51% by mass. Table 1 shows the results of measuring the permeability coefficient and ideal separation coefficient of various gases at 35°C for the organic-inorganic hybrid membrane M-3.
[0123] Furthermore, the aspect ratio measured by the first method in the particle cross-section of the metal-organic framework of Comparative Example 1, as measured by the evaluation method described above, was 1.6, and the aspect ratio measured by the second method was 1.4. The average particle size calculated by the first method described above was 1.0 μm, and the average particle size calculated by the second method was 1.5 μm.
[0124] [Reference Example 1] (Silicone resin film M-4) As a reference example 1, a silicone resin film M-4 that does not contain MOF was fabricated, and the glass transition temperature of the silicone resin film M-4 was evaluated. 2.0 g of hexane (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and 0.63 g of poly(dimethylsiloxane), (hydroxy-terminated silicone resin P-1, viscosity: 18,000-22,000 cSt, manufactured by Sigma-Aldrich Japan) were mixed using a stirring bar until homogeneous. Then, 0.14 g of tetraethyl orthosilicate (manufactured by Tokyo Chemical Industry Co., Ltd.) and 0.015 g of dibutyltin dilaurate (manufactured by Sigma-Aldrich Japan) were added and mixed thoroughly. The entire resulting mixture was dropped into a 30 mm inner diameter Teflon® petri dish, and the Teflon® petri dish was placed in a vacuum dryer to evaporate the hexane. After that, it was left to stand overnight in a fume hood to cure the matrix resin, hydroxy-terminated silicone resin P-1. The film was peeled off the Teflon® petri dish to obtain a silicone resin film M-4. The film thickness was 159 μm. The glass transition temperature (Tg) of the silicone resin film M-4 was measured using a DSC600 (differential scanning calorimeter, manufactured by Hitachi High-Tech Science Corporation) and found to be -124°C.
[0125] [Fabrication of organic-inorganic hybrid films] Table 1 shows the results of measuring the permeability coefficient and ideal separation coefficient of various gases at 35°C for each of the organic-inorganic hybrid membranes M-1, M-2, and M-3, which were prepared using the Zn-MOF of Examples 1 and 2 and Comparative Example 1. Table 1 shows the aspect ratio measured by Method 1 and the evaluation results of the permeability coefficient and ideal separation coefficient, while Table 2 shows the aspect ratio measured by Method 2 and the evaluation results of the permeability coefficient and ideal separation coefficient.
[0126] [Table 1]
[0127] [Table 2]
[0128] As shown in Tables 1 and 2, the organic-inorganic hybrid membranes M-1 and M-2 of Examples 1 and 2 have higher ideal separation coefficients for H2 / CH4 and He / CH4 compared to the organic-inorganic hybrid membrane M-3 of Comparative Example 1. In the case of H2 / CH4 and He / CH4, the separation is due to differences in molecular size, and by using the plate-shaped MOF with a large aspect ratio of the present invention, it becomes possible to separate even gases with low adsorption performance with high separation performance. Furthermore, even when evaluated by the more accurate second method, the organic-inorganic hybrid membranes M-1 and M-2 of Examples 1 and 2 were confirmed to have a larger aspect ratio of 1.7 or higher than the organic-inorganic hybrid membrane M-3 of Comparative Example 1, just as when evaluated by the first method. [Industrial applicability]
[0129] This disclosure can be applied, for example, to membranes used in membrane separation methods for efficiently recovering hydrogen (H2) and helium (He), and represents a technology of high industrial value.
Claims
1. A metal-organic framework containing a metal to which two or more ligands coordinate, A metal-organic framework in which the ratio of the major axis to the minor axis in the particle cross-section of the metal-organic framework is 1.7 or greater.
2. The metal-organic framework according to claim 1, wherein the metal is zinc.
3. The metal-organic framework according to claim 1, wherein the metal to which the ligand coordinates includes triazolates and oxalates.
4. An organic-inorganic hybrid film comprising a metal-organic framework containing a metal to which two or more ligands coordinate, and a resin, An organic-inorganic hybrid film in which the ratio of the major axis to the minor axis in the particle cross-section of the metal-organic framework is 1.7 or more, and the content of the metal-organic framework is 30% by mass or more.
5. The organic-inorganic hybrid film according to claim 4, wherein the glass transition temperature of the resin is 15°C or lower.
6. A composition for forming organic-inorganic hybrid films, The system includes a metal-organic framework containing a metal to which two or more ligands coordinate, and a resin. A composition in which the ratio of the major axis to the minor axis in the particle cross-section of the metal-organic framework is 1.7 or more, and the content of the metal-organic framework is 30% by mass or more.
7. A method for manufacturing a metal-organic framework, The reaction solution before the reaction of the metal-organic framework contains a coordination compound and a carboxylic acid compound. The carboxylic acid compound is a formic acid compound, or a method for producing a carboxylic acid compound comprising at least two types of carboxylic acid compounds.
8. The reaction solution contains a metal compound, The carboxylic acid compound is selected from formic acid and formate salts. The method for producing a metal-organic framework according to claim 7, wherein the formate is sodium formate.
9. The method for producing a metal-organic framework according to claim 7, wherein the carboxylic acid compound is zinc formate.
10. The aforementioned metal compound is dissolved in 100 cm³ of water at 25°C. 3 A method for producing a metal-organic framework according to claim 8, wherein the zinc compound has a solubility of 0.05 g or more in relation to .
Citation Information
Patent Citations
Metal-organic frameworks, their manufacture and use
JP2016516677A
Synthesis of zinc MOF materials
JP2021522226A